Proceedings of the First International Conference on Progressive Civil Society (ICONPROCS 2019) 2019
DOI: 10.2991/iconprocs-19.2019.42
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Work Satisfaction with Employee Engagement

Abstract: Job satisfaction is a factor capable of increasing the level of employee engagement. This study aims to empirically examine the relationship between job satisfaction and employee engagement. The subjects in this study are the lecturers at the University of X. The selection of subjects was randomized and the sampling technique was randomized sampling. Methods of data collection were the scale of job satisfaction and employee engagement scale. The data were analyzed using product moment correlation techniques. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…These results suggest that having a robust socio-interpersonal competency base can positively contribute to an individual's socio-cultural adaptability. The results further agree with the study conducted by Tentama et al (2019) showing a significant link between work satisfaction and relationships, as well as the study by Saunders and Bajjaly (2022) Table 11 shows the test of difference between IT competencies and the respondents' characteristics. Based on this table, the overall test of significant difference using MANOVA showed only significant differences found in the IT-related competencies when respondents were grouped according to Job Position levels (f = 4.72, p < 0.001).…”
Section: 03 Much Satisfiedsupporting
confidence: 90%
See 1 more Smart Citation
“…These results suggest that having a robust socio-interpersonal competency base can positively contribute to an individual's socio-cultural adaptability. The results further agree with the study conducted by Tentama et al (2019) showing a significant link between work satisfaction and relationships, as well as the study by Saunders and Bajjaly (2022) Table 11 shows the test of difference between IT competencies and the respondents' characteristics. Based on this table, the overall test of significant difference using MANOVA showed only significant differences found in the IT-related competencies when respondents were grouped according to Job Position levels (f = 4.72, p < 0.001).…”
Section: 03 Much Satisfiedsupporting
confidence: 90%
“…Research carried out by Tentama et al (2019) found a significant link between work satisfaction and relationships. All of these have similar bearings in the areas of concern of this present research as it dwelt on the correlation between job satisfaction and work competencies in technical aspects, management and social and interpersonal relationships.…”
Section: Socio-cultural Adaptabilitymentioning
confidence: 97%
“…Satisfaction with salary has been positively related to achieving employee engagement (Tentama et al 2019;Raralio 2022;Tugade and Arcinas 2023). In other words, monetary rewards, including salary, have been identified as important factors that influence job satisfaction and employee motivation (Chinyio et al 2018).…”
Section: Satisfaction With Salary and Employee Engagementmentioning
confidence: 99%